Effects of different exercise modalities on cardiac dysfunction in heart failure with preserved ejection fraction. (25th March 2021) - Bode, David; Rolim, Natale P.L.; Guthof, Tim; Hegemann, Niklas; Wakula, Paulina; Primessnig, Uwe; Berre, Anne Marie Ormbostad; Adams, Volker; Wisløff, Ulrik; Pieske, Burkert M.; Heinzel, Frank R.; Hohendanner, Felix; et al.
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) is an increasingly prevalent disease. Physical exercise has been shown to alter disease progression in HFpEF. We examined cardiomyocyte Ca 2+ homeostasis and left ventricular function in a metabolic HFpEF model in sedentary and trained rats following 8 weeks of moderate‐intensity continuous training (MICT) or high‐intensity interval training (HIIT). Methods and results: Left ventricular in vivo function (echocardiography) and cardiomyocyte Ca 2+ transients (CaTs) (Fluo‐4, confocal) were compared in ZSF‐1 obese (metabolic syndrome, HFpEF) and ZSF‐1 lean (control) 21‐ and 28‐week‐old rats. At 21 weeks, cardiomyocytes from HFpEF rats showed prolonged Ca 2+ reuptake in cytosolic and nuclear CaTs and impaired Ca 2+ release kinetics in nuclear CaTs. At 28 weeks, HFpEF cardiomyocytes had depressed CaT amplitudes, decreased sarcoplasmic reticulum (SR) Ca 2+ content, increased SR Ca 2+ leak, and elevated diastolic [Ca 2+ ] following increased pacing rate (5 Hz). In trained HFpEF rats (HIIT or MICT), cardiomyocyte SR Ca 2+ leak was significantly reduced. While HIIT had no effects on the CaTs (1–5 Hz), MICT accelerated early Ca 2+ release, reduced the amplitude, and prolonged the CaT without increasing diastolic [Ca 2+ ] or cytosolic Ca 2+ load at basal or increased pacing rate (1–5 Hz). MICT lowered pro‐arrhythmogenic Ca 2+ sparks and attenuated Ca 2+ ‐wave propagation in cardiomyocytes. MICT was associated with increased stroke volume in HFpEF. Conclusions: In this metabolic rat model of HFpEF at an advanced stage, Ca 2+ release was impaired under baseline conditions. HIIT and MICT differentially affected Ca 2+ homeostasis with positive effects of MICT on stroke volume, end‐diastolic volume, and cellular arrhythmogenicity.